Filantropi Islam Digital Dalam Perspektif Opini Publik Muslim Perkotaan: Analisis Manajemen Dan Kepercayaan - Mubasit; Nasution, Nadya Amalia (STAI Bumi Silampari, 2025)
Islamic philanthropy has undergone significant transformation in the digital era, presenting new opportunities and challenges in building public trust. This study employed a mixed-methods approach, combining a quantitative survey of 100 donors to the National Azan Zakat Agency (BAZNAS) in Bandar Lampung City with in-depth interviews with 15 participants. The quantitative analysis included linear regression, while the qualitative data were analyzed thematically. Secondary data from BAZNAS reports and policy documents were also used to enrich the analysis. This study aimed to analyze the perceptions and levels of trust among urban Muslims in digital Islamic philanthropy management, identify challenges, and identify influencing factors. The results showed that levels of trust in digital Islamic philanthropy management varied based on donor age. Younger donors (18-35 years old) tended to trust digital platforms more, while older donors (>50 years old) preferred traditional methods. Other factors influencing trust include education level, digital literacy, and previous experience with philanthropic institutions. Financial transparency, platform ease of use, and the institution's reputation are also key factors in building trust. Bridging the digital divide between generations, increasing digital literacy among senior donors, and ensuring data security are particular challenges for institutions. Philanthropic institutions need to adopt a multi-channel strategy that accommodates the preferences of various age groups while maintaining Sharia principles.